Promoting audit transparency in higher education through an internal academic quality audit application - Yulianti, Dwi; Dewi, Indah Kusuma; Wahdi, Yera Wahda (Researcher and Lecturer Society, 2024)
This study aims to design and develop a web-based application for Internal Quality Audit at Universitas Ibnu Sina, replacing the conventional audit process which is currently in use. The previous manual audit process resulted in inefficiencies and increased the risk of errors. Key challenges identified include limitations in human resources, time, and funding, as well as the low effectiveness of the audit process. In order to address these issues, the proposed information system facilitates the distribution of online checklists and document uploads, thereby expediting the verification and reporting audit results. This research adopts the System Development Life Cycle (SDLC) approach in its development, utilizing methods that include use case diagrams, activity diagrams, sequence diagrams, and database design. These methods enhance interaction and workflow within the audit team. Testing results indicate that the system functions to the expected specifications. Furthermore, this study demonstrates that implementing a web-based system can accelerate reporting, improve the structure and documentation of audits, and support efforts to enhance academic quality at the university. Implementing this system is expected to increase efficiency and accuracy in the academic quality audit process at Universitas Ibnu Sina.